2012
DOI: 10.3109/10520295.2012.717304
|View full text |Cite
|
Sign up to set email alerts
|

Staining tumor cells with biotinylated ACL-I, a lectin isolated from the marine sponge, Axinella corrugata

Abstract: Axinella corrugata lectin 1 (ACL-1) was purified from aqueous extracts of the marine sponge, Axinella corrugata. ACL-1 strongly agglutinates native rabbit erythrocytes. The hemagglutination is inhibited by N-acetyl derivatives, particularly N, N', N"-triacetylchitotriose, N-acetyl-D-glucosamine, N-acetyl-D-mannosamine and N-acetyl-D-galactosamine. We investigated the capacity of biotinylated ACL-1 to stain several transformed cell lines including breast (T-47D, MCF7), colon (HT-29), lung (H460), ovary (OVCAR-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The lectin can be used as a marker diagnostic and also tissue mapping tool in suspicious neoplasms. As biotinylated ACL-I could stain the tumor cells, it might be used to identify transformed cells and study the glycan structures synthesized by such cells (Dresch et al 2013). One characteristic of malignant cells is related to abnormal cell surface protein glycosylation.…”
Section: Other Medicinal Applicationsmentioning
confidence: 99%
“…The lectin can be used as a marker diagnostic and also tissue mapping tool in suspicious neoplasms. As biotinylated ACL-I could stain the tumor cells, it might be used to identify transformed cells and study the glycan structures synthesized by such cells (Dresch et al 2013). One characteristic of malignant cells is related to abnormal cell surface protein glycosylation.…”
Section: Other Medicinal Applicationsmentioning
confidence: 99%
“…In addition to mitogenic activity, ACL-1 can also be used as a tool for mapping tissue suspected of neoplasia. The results found by Dresch showed that this lectin complexed with biotin is able to recognize breast (T-47D, MCF7), colon (HT-29), lung (H460), ovarian (OVCAR-3) and bladder cancer cells (T24) by binding GalNAc and GlcNAc to the surface of these cells [31].…”
Section: Biological Applications Of Lectins From Marine Spongementioning
confidence: 99%
“…Sea worm Serpula vermicularis GlcNAc binding lectin was determined to be effective in inhibiting HIV-1 infection [20]. Marine sponge Axinella corrugate-1 is a GlcNAc binding lectin showing chemotactic effect on rat neutrophil [21], and was utilized in staining various cancer cells [22]. Abnormal GlcNAc glycosylation has been identified as a cancer maker [23], and utilized in bladder cancer targeting drug delivery [24] and cancer cell staining [22].…”
Section: Introductionmentioning
confidence: 99%
“…Marine sponge Axinella corrugate-1 is a GlcNAc binding lectin showing chemotactic effect on rat neutrophil [21], and was utilized in staining various cancer cells [22]. Abnormal GlcNAc glycosylation has been identified as a cancer maker [23], and utilized in bladder cancer targeting drug delivery [24] and cancer cell staining [22]. A GlcNAc specific lectin purified from the fruiting body of the Australian indigenous mushroom Psathyrella asperospora inhibited HT29 cancer cells proliferation through inducing cell cycle arrest at G2/M phase [25].…”
Section: Introductionmentioning
confidence: 99%